Pengembangan Intrapreneurial Employee Pada Perusahaan Bumd Dengan Menggunakan Soft Systems Methodology - Agustyo Nugroho; Effy Z. Rusfian; Rachma Fitriati (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Regionally owned Business Enterprises (BUMD) companies in their operations are not only profit-oriented but also have a role as providers of tasks assigned by the regional government. This is what causes BUMD companies such as PT Jakarta Propertindo to be able to make adjustments to the company's development plans, thereby causing the company to experience unfavorable conditions. The company's unfavorability affects the intrapreneurial behavior of its employees. This research uses a qualitative method with a Soft Systems Methodology approach. By paying attention to factors developing employee intrapreneurial behavior, problem solving focuses on these matters. This research resulted in solving the problem of PT Jakarta Propertindo which received intervention from the regional government, namely by making provisions and regulations for company development planning so that the company could be conducive to carrying out operations based on this plan. Having a comfortable work environment is the key to developing intrapreneurial behavior. Providing Leadership Development Program training is an encouragement for developing intrapreneurial behavior at PT Jakarta Propertindo